Healthcare Provider -Patient Communication Techniques and Cervical Cancer Management at Moi Teaching and Refferal Hospital Cancer Center - Kebenei, Dorcas; Nyambane, Rhoydah; Mutua, Joan (International Journal of Communication and Public Relation, 2024)
Purpose: The study examined the effect of communication techniques in healthcare provider-patient communication on management of cervical cancer among women seeking treatment at Chandaria Centre, Moi Teaching and Referral hospital in Kenya. The main objectives of the study was to was to examine the contribution of healthcare provider-patient communication on management of cervical cancer among women seeking treatment at Moi teaching and referral hospital cancer centre. Methodology: The study was supported by the health belief model. A descriptive research design was used through a mixed method approach to generate and analyze data. Systematic random sampling was used to select 320 respondents in the study for quantitative data while purposive sampling was used to identify 10 respondents for qualitative data. Structured questionnaires and interviews were used to generate data for the proposed study. Quantitative analyses was done using statistical package for social sciences (SPSS) tool version 25. Qualitative data was analyzed thematically in line with study themes/objectives. Findings: The study found out that communication techniques applied by health care provider and patients had significant effects on the uptake of cervical cancer management among women seeking treatment at Moi Teaching and Referral hospital cancer centre. Unique Contribution to Theory, Practice and Policy: The study recommended that there is need for significant improvements in communication strategies used by those dealing with patients, especially those suffering from terminal illnesses since their communicative responses had a significant impact on how they respond to treatment and management. The study also recommended that healthcare providers need to be sensitive to cross-cultural communication so as to reduce the incidences of misinterpretation.